2013
DOI: 10.1007/s00436-013-3515-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression, immunolocalization and serodiagnostic value of Tc38630 protein from Trypanosoma congolense

Abstract: Animal African trypanosomosis is a serious constraint to livestock sector development in sub-Saharan Africa. The disease, mainly caused by Trypanosoma congolense, has a limitation in its diagnosis and treatment. There is urgent need for a simple, rapid detection technique to replace the few available serological tests that are of variable sensitivity and specificity. Currently, there is a promising use of recombinant proteins to improve on the trypanosome lysate to detect antibodies. In this respect, we have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is worth noting that it has been previously reported that this antigen does not cross react with the common non-pathogenic cattle trypanosome T. theileri [11].…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…It is worth noting that it has been previously reported that this antigen does not cross react with the common non-pathogenic cattle trypanosome T. theileri [11].…”
Section: Resultsmentioning
confidence: 91%
“…Nevertheless, three proteins belonging to the invariant surface glycoprotein (ISG) family (Tc38630, Tc45510 and Tc29290) were successfully identified as potential diagnostic antigens by proteomic selection followed by assessment of likely ease of expression in E. coli followed by protein expression trials. The best performing of these, Tc38630, was also recently reported as a potential diagnostic antigen for T. congolense infections using experimental mouse sera [11]. Although annotated as hypothetical in the genome database, Tc38630 has been previously identified by quantitative proteomics as being most abundant on the metacyclic and bloodstream trypomastigote forms of T. congolense [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…brucei gambiense and cattle T . congolense infections [ 10 12 ]. One of these antigens, a recombinant invariant surface glycoprotein (rISG65-1), has been selected by the Foundation for Innovative New Diagnostics (FIND) for development of a next-generation ‘all recombinant’ LFT for human African trypanosomiasis.…”
Section: Introductionmentioning
confidence: 99%